OP0260 Targeting CD1C-Expressing MDCS to Inhibit T Cell Activation and Thymus and Activation Regulated Chemokine (TARC)-Dependent Chemotaxis in RA. (23rd January 2014) - Hillen, M. R.; Moret, F. M.; Lafeber, F. P.; Hack, C. E.; Radstake, T. R.; van Roon, J. A.
Abstract : Background: Recently, we demonstrated strong Th1 and Th17 cytokine induction by CD1c + myeloid dendritic cells (mDCs) from synovial fluid and identified thymic stromal lympopoeitin (TSLP) as an important activator of these cells. CD1c-expressing mDCs and CD4 T cells are potent producers of Thymus and activation regulated chemokine (TARC), which is a chemotactic factor that attracts cells expressing CCR4, including CD4 T cells with Th2, Th17 and Treg phenotypes. TARC is known as a critical mediator in atopic diseases but is also present at sites of inflammation in autoimmune diseases. In synovial fluid (SF) of rheumatoid arthritis (RA) patients CCR4 is expressed on Th17 cells and mast cells that together are indicated to make up most IL-17 producing cells, suggesting that TARC plays an important role in attraction of IL-17 producing cells to the synovium. In addition, TARC can attract mDCs and fibroblasts. Objectives: To investigate if TARC is associated with RA pathogenesis and whether depletion of CD1c mDCs prevents production of high TARC concentrations. Methods: TARC ELISA was performed on SF of 100 RA and 50 OA patients. Mononuclear cells (MC) were isolated from the blood of healthy controls (HC) and blood or SF of RA patients and juvenile idiopathic arthritis (JIA) patients. CD1c mDCs were isolated with MACS and stimulated with TSLP for 24 hours and TARC levels were measured in supernatants. Alternatively, CD1c-expressing cells were depleted from MC using MACS and TARC levels were measured upon stimulation with TSLP or IL-7 (n=6). Results: SF from RA patients contained significantly higher concentrations of TARC as compared to SF from OA patients (78.9 vs 9.2 pg/mL, p<0.0001). Isolated CD1c mDCs from the synovial fluid of RA patients produced TARC directly ex vivo and produced significantly higher TARC levels compared to paired mDCs from the blood (26.4 vs 1.2 pg/mL, p<0.01). CD1c mDCs and SFMCs from RA and JIA patients produced more TARC compared to paired PB counterparts when stimulated with TSLP (926 vs 128 pg/mL, p<0.01) (or IL-7, p<0.01). Moreover, depletion of CD1c cells from MC significantly reduced TARC production induced by stimulation with TSLP (mean inhibition 76%, p=0.031). Conclusions: Increased TARC levels correlate with the percentages of CD1c-expressing mDCs present in RA SF; these mDCs produce enhanced TARC levels directly ex vivo and production is increased upon stimulation with TSLP. TARC production is markedly decreased when CD1c cells are depleted. Considering the strong potential of SF CD1c + mDCs to activate CD4 T cells and to induce Th1 and Th17 cytokine secretion as well as the potent attraction of a range of inflammatory cells by TARC, targeting CD1c mDCs could be a novel therapeutic approach in RA. Disclosure of Interest: None Declared